Eksperimen Pembelajaran Matematika Dengan Metode Student Team Achievement Division (Stad) Dan Numbered Head Together (Nht) Terhadap Hasil Belajar Ditinjau Dari Keaktifan Siswa Kelas VII SMP Negeri 23 SurakartaSemester Gasal Tahun 2016/2017 - Aminingsih, Ayu; , Drs.Slamet H.W, M.M, M.Pd (2017)
ABSTRACT Ayu Aminingsih / A410130150. EKSPERIMEN PEMBELAJARAN MATEMATIKA DENGAN METODE STUDENT ACHIEVEMENT DIVISION (STAD) DAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR DITINJAU DARI KEAKTIFAN SISWA KELAS VII SMP NEGERI 23 SURAKARTA SEMESTER GASAL TAHUN 2016/2017. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Desember, 2016. The purpose of the research are to analyze: (1) the effect of learning methods Student Team Achievement Division (STAD) and Numbered Head Together (NHT) on learning outcomes. (2) the effect student active for learning outcomes. (3) the interaction between learning methods Student Team Achievement Division (STAD) and Numbered Head Together (NHT) terms of active on learning outcomes. Type of the reseach quantitative with quassi experimental design. Sample where taken by Cluster random sampling of the population of all students of class VII SMP Negeri 23 Surakarta academic year 2016/2017. Data collection techniques by using questionnaires, tests and documentation. Before to the analyze, first tested the normality and homogeneity test. The hypotesistent use unvalance two way analysis of variance with α = 5%. The result of this study showed: (1) there was the effect of learning methods Student Team Achievement Division (STAD) and Numbered Head Together (NHT) on learning outcomes. (2) there was the effect student active for learning outcomes. (3) there was not interaction between learning methods Student Team Achievement Division (STAD) and Numbered Head Together (NHT) terms of active on learning outcomes. Keywords: learning outcomes, NHT, STAD, student active